Queer African Cinemas - Green-Simms, Lindsey B. (Duke University Press, 2022)
In Queer African Cinemas, Lindsey B. Green-Simms examines films produced by and about queer Africans in the first two decades of the twenty-first century in an environment of increasing antiqueer violence, efforts to criminalize homosexuality, and other state-sanctioned homophobia. Green-Simms argues that these films not only record the fear, anxiety, and vulnerability many queer Africans experience; they highlight how queer African cinematic practices contribute to imagining new hopes and possibilities. Examining globally circulating international art films as well as popular melodramas made for local audiences, Green-Simms emphasizes that in these films queer resistance-contrary to traditional narratives about resistance that center overt and heroic struggle-is often practiced from a position of vulnerability. By reading queer films alongside discussions about censorship and audiences, Green-Simms renders queer African cinema as a rich visual archive that documents the difficulty of queer existence as well as the potentials for queer life-building and survival.